Quantum oscillations probe the Fermi surface topology of the nodal-line semimetal CaAgAs - Coldea, A; Kwan, Y; Reiss, P (University of Oxford, 2020)
These data accompany the manuscript entitled: "Quantum oscillations probe the Fermi surface topology of the nodal-line semimetal CaAgAs" arXiv:2001.02434 by Y. Kwan et al to be published in Physical Review Research 2020. The quantum oscillations data were obtained using the torque magnetometry technique and were collected at high magnetic field facilities, at HFML in Nijmegen up to 35T and NHMFL Tallahassee up to 45T. Measurements were performed using Helium 3 cryostat and single-axis rotators. Band structure calculations were performed using the experimental details of CaAgAs and Wien2k. Other modelling of the data is described in detail in the Supplemental Material of the paper (arXiv:2001.02434).